2000
DOI: 10.1073/pnas.140210697
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factors: An epigenetic mechanism of broad spectrum resistance to anticancer drugs

Abstract: Based on the observation that removal of tumors from metastatic organs reversed their chemoresistance, we hypothesized that chemoresistance is induced by extracellular factors in tumor-bearing organs. By comparing chemosensitivity and proteins in different tumors (primary vs. metastases) and different culture systems (tumor fragment histocultures vs. monolayer cultures derived from the same tumor), we found elevated levels of acidic (aFGF) and basic (bFGF) fibroblast growth factors in the conditioned medium (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(117 citation statements)
references
References 26 publications
2
112
0
3
Order By: Relevance
“…Of note, in prostate cancer cell lines, the levels of FGF-2 and FGFR1 have been shown to increase proportionally to the degree of cancer aggressiveness and castration resistance (Nakamoto et al, 1992;Cronauer et al, 1997). The analysis of tumor specimens has shown that enhanced FGF signaling results in increased proliferation, invasiveness and resistance to therapy in several solid and hematological malignancies (Menzel et al, 1996;Konig et al, 1997;Song et al, 2000;Sezer et al, 2001;Acevedo et al, 2009;Turner et al, 2010). Moreover, hemi-or homozygous inactivation of Fgf-2 alleles in TRAMP mice with transgenic prostate adenocarcinoma resulted in increased survival by inhibiting progression toward a poorly differentiated and highly metastatic phenotype (Polnaszek et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in prostate cancer cell lines, the levels of FGF-2 and FGFR1 have been shown to increase proportionally to the degree of cancer aggressiveness and castration resistance (Nakamoto et al, 1992;Cronauer et al, 1997). The analysis of tumor specimens has shown that enhanced FGF signaling results in increased proliferation, invasiveness and resistance to therapy in several solid and hematological malignancies (Menzel et al, 1996;Konig et al, 1997;Song et al, 2000;Sezer et al, 2001;Acevedo et al, 2009;Turner et al, 2010). Moreover, hemi-or homozygous inactivation of Fgf-2 alleles in TRAMP mice with transgenic prostate adenocarcinoma resulted in increased survival by inhibiting progression toward a poorly differentiated and highly metastatic phenotype (Polnaszek et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their roles in tumor formation and progression, FGF and FGFR also act as key regulators of angiogenesis (2,(22)(23)(24), especially during tumor growth. Upregulation of FGF/FGFR signaling activity also leads to resistance to antiangiogenic and other chemotherapies (12,(25)(26)(27)(28). Together, the FGF/FGFR pathway is essential to cancer cells, and inhibition of this pathway therefore offers potential clinical utilities for treating various types of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The FGF-2 has been shown to prevent cell death induced by several chemotherapeutic agents including paclitaxel, doxorubicin and 5-flurouracil in human prostate cancer cells and rat tumors (19). However, the underlying mechanism has not been clearly elucidated.…”
Section: Discussionmentioning
confidence: 99%